Mathematical Understanding in Problem Solving as Viewed through the Lens of Mathematics Anxiety among Elementary School Students - Choiriah, Siti; Amelia Amri, Mira; Yunus, M (Media Pendidikan Matematika, 2025)
This study aims to examine students’ mathematical understanding in solving mathematical problems viewed from their levels of mathematical anxiety. The research employed a qualitative descriptive approach and was conducted at MI Attaqwa 26 Bekasi with 33 fifth-grade (VA) students as research subjects. The instruments used in this study consisted of a mathematical anxiety questionnaire to categorize students’ anxiety levels, a geometry problem-solving test to assess students’ mathematical understanding, and semi-structured interviews to explore students’ reasoning processes in depth. Data were collected through questionnaires, written tests, and interviews, and were analyzed using qualitative data analysis techniques, including data reduction, data presentation, and conclusion drawing. The results of the study indicate that students with high mathematical anxiety were still able to demonstrate good mathematical understanding, as they could correctly interpret mathematical concepts and symbols, connect mathematical concepts to construct meaningful knowledge, explain mathematical ideas in their own words, apply concepts to new problem situations, and draw conclusions as well as generalize mathematical principles to solve various types of geometry problems. These findings suggest that high mathematical anxiety does not necessarily impede students’ mathematical understanding in problem-solving activities.